Local Solidarities: How the Arab Spring Protests Started. (23rd August 2019) - Charrad, Mounira M.; Reith, Nicholas E.
Abstract : Coming as a surprise to most observers and following the self‐immolation of a street vendor in a remote town of central Tunisia, the Jasmine Revolution of 2010–2011, the first uprising of the Arab Spring, has often been seen as a success story for digital communication through widespread use of social media. We suggest that this applied to the later phase of the protests in Tunisia but not to the initial phase, which occurred in local areas in impoverished and marginalized regions with highly limited access to the Internet. The initial phase lasted a full 10 days before the protests reached major cities where social media operated. Building on Tilly's concept of trust network, we offer the concept of local solidarities as key to the beginning of the Arab Spring uprisings and as encompassing spatial proximity, shared marginalized status, and kinship, all of which combined to serve as a basis for trust and collective action.